Effect of disinfection and storage on the flexural strength of ocular prosthetic acrylic resins - Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Moreno, Amalia; Iyda, Mariana G.; Rezende, Maria Cristina Rosifini Alves [UNESP]; Haddad, Marcela F. (Wiley-Blackwell, 2012)
Objective: To evaluate the influence of chemical disinfection and storage duration on the flexural strength of acrylic resins commonly used to make ocular prostheses.Methods: A total of 260 samples were manufactured with N1 resin and colourless resin. Both resins were thermopolymerised using a microwave oven. Samples were stored and periodically disinfected and were divided into groups: control (no disinfection) (I), neutral soap (II), Opti-free (III), Efferdent (IV), 1% hypochlorite (V) or 4% chlorhexidine (VI). The flexural strength was measured before and after 60 and 120 days of storage. Data were analysed by ANOVA and Tukey test (0.05).Results: The flexural strength of the N1 resin was higher than that for the colourless resin. There was a significant difference in the flexural strength before and after 60 and 120 days of storage with disinfection, regardless of the resin and disinfectant. Group I in the initial period exhibited greater flexural strength, with significant difference only in group VI after 120 days.Conclusion: It can be concluded that the flexural strength only changed after 120 days of storage for samples disinfected with chlorhexidine. However, all flexural strength values obtained herein were acceptable clinical limits for the acrylic resins.
Keywords: artificial eye; acrylic resin; flexural strength; chemical disinfection